Financing for development series: Southern Non-DAC Actors in development cooperation - Tatjana Chahoud (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
Since the beginning of the 21st century the world has been witnessing new dynamics in international development cooperation. Additional actors, mainly from the South, have emerged or re-emerged and are challenging the traditional donor-recipient modality. Understanding these changes calls for greater transparency of the role played by southern non-DAC actors and their impact in the field of development cooperation. However, in assessing the role of non-DAC actors, we face two challenges in particular: – There is no globally a greed definition of what constitutes development assistance/development cooperation. – Many southern countries do not publicise their development assistance activities, with the result that reporting is unclear and transparency is lacking. With these constraints taken into account, an analysis of available data and documents shows the main features of southern non-DAC development cooperation policies to be as follows: - The development cooperation policies of most non-DAC actors are based on a more holistic approach than classical Official Development Assistance (ODA) policies. Southern provision of development assistance is not strictly separated from the countries' trade and investment activities. A simple analysis of the development cooperation policies of southern providers from an ODA point of view therefore falls short of revealing the new role played by southern actors. – Most southern non-DAC actors accept the Aid Effectiveness Agenda as recipient countries, but do not see it as a frame work for their own bilateral development cooperation activities. – Among non-DAC actors the volume and scope provided to developing countries varies considerably. In financial terms the most relevant southern non-DAC providers are China, India, Venezuela and Saudi Arabia, each providing around US 1bn annually. – In contrast to the Organisation for Economic Co-operation and Development/Development Assistance Committee (OECD/DAC), southern development cooperation policies have specific characteristics which differ from classical donors' provisions. The sectoral focus of financial flows is mainly on infrastructure, and most contributions are provided on the basis of non-interference, i.e. they are not linked to any such conditions as “good governance” and human rights. To unlock the full potential of international development cooperation, ongoing dialogues between the OECD/DAC donors and southern non-DAC actors should be intensified. These dialogues in multilateral fora and more examples of triangular cooperation will be needed to ensure transparency and to avoid failures to comply with existing environmental and social standards in development cooperation.
Keywords: 330